ELEVATED HOMOCYSTEIN LEVELS AS A RISK FACTOR FOR THE DISEASE IN CEREBRAL ISCHEMIA - Khaydarova Dildora Kadirovna; Xatamova Sarvinoz Muyitdinovna (Scholar Express Journals, 2023)
The amino acid homocysteine (HC), which is a product of methionine demethylation, has been of particular interest to researchers for about half a century. HC is a sulfur-containing amino acid synthesized endogenously from methionine. The article describes the role of homocysteine and the problem of hyperhomocysteinemia in the development of cognitive impairment in cerebrovascular diseases and chronic ischemic ischemia.
Keywords: hyperhomocysteinemia; homocystein; remethylation; neurotransmitter monoamines